PENGARUH PEMANFAATAN PETA BERBASIS BENCANA TERHADAP HASIL BELAJAR GEOGRAFI KELAS XI SMAN 3 PONTIANAK - Rheswagiri, Pracikal; Sulistyarini, Sulistyarini; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to analyze the effect of utilizing disasters Based-maps outcomes learning geography XI class in SMAN 3 Pontianak. The research method that used is experimental research which is quasy experimental with nonequivalent control group design. The populasion of this research is the whole of the XI class in SMAN 3 Pontianak with total 94 students. The sample of this research are XI IPS 2 class (experiment) and XI IPS 1 class (control). The average learning outcomes of post-test class experiment is 72,24 and class control is 66,12 and acquired is 2,440 and ? = 5% is 1,671. So, (2,440) > (1,671). Then, Ha is accepted. It can be concluded that there is the effect of the effect of utilizing disasters Based maps outcomes learning in geography XI class SMAN 3 Pontianak. the result of effect size is 0,69 (medium criteria). It means that learning by utilizing disasters Based maps gives high effect to the learning outcomes of Student XI Class in SMAN 3 Pontianak.Keywords: Disasters Based-Maps, Learning Media, Learning Outcomes.